THE EFFECT OF TREATMENT OF UNMALTED BARLEY ON THE FRACTIONAL NITROGEN COMPOSITION OF BEER WORT - Кhokonova Madina; Adzhieva, Aida (Revista Inclusiones, 2020)
The correctness of breakdown of protein substances in raw materials during mashing is as important for the production of wort and beer of normal composition as that of starch. Abnormal breakdown of proteins leads to a sharp deterioration in the organoleptic characteristics of beer and a decrease in its stability. The study aims to determine the effect of pre-treatment of unmalted barley on the fractional nitrogen composition of the resulting wort. As a result of the studies, an increase in the content of total soluble nitrogen occurring evenly due to all fractions has been observed. However, it is noticeable that the higher the amount of unmalted barley in the mash, the greater the increase in total soluble nitrogen due to the high molecular weight nitrogenous substances of fraction A. Amine nitrogen content in the wort does change after the increase in the processing temperature of unmalted barley from 100 to 138°С, and it only slightly decreases with further increase in temperature, which occurs due to an increase in the reaction of melanoidins formation. The ratio of A and B soluble nitrogen fractions in the wort slightly increase depending on the processing temperature of unmalted barley and its proportion in the mash. The exception is the case with 40% content of unmalted barley.